Realistic Affective Forecasting: The Role of Personality - Hoerger, Michael (Cogn Emot, 2015)
Affective forecasting often drives decision making. Although affective forecasting research has often focused on identifying sources of error at the event level, the present investigation draws upon the ‘realistic paradigm’ in seeking to identify factors that similarly influence predicted and actual emotions, explaining their concordance across individuals. We hypothesized that the personality traits neuroticism and extraversion would account for variation in both predicted and actual emotional reactions to a wide array of stimuli and events (football games, an election, Valentine’s Day, birthdays, happy/sad film clips, and an intrusive interview). As hypothesized, individuals who were more introverted and neurotic anticipated, correctly, that they would experience relatively more unpleasant emotional reactions, and those who were more extraverted and less neurotic anticipated, correctly, that they would experience relatively more pleasant emotional reactions. Personality explained 30% of the concordance between predicted and actual emotional reactions. Findings suggest three purported personality processes implicated in affective forecasting, highlight the importance of individual-differences research in this domain, and call for more research on realistic affective forecasts.